“An Odyssey of Third Space Endoscopy”—from Entry into the Tunnel to Entry into the Peritoneal Cavity - Mandavdhare, Harshal S.; Mishra, Shubhra; Samanta, Jayanta; Shah, Jimil; Kochhar, Rakesh (Journal of Digestive Endoscopy, 2019)
The last decade has seen the growth of a completely new and exciting entity called the third space endoscopy (TSE) that has brought about a paradigm shift in the way we manage various disorders of the gastrointestinal tract. The journey started with per oral endoscopic myotomy (POEM) for achalasia cardia and within a decade the concept has been exploited to its best potential for disorders including submucosal tumor resection, pyloromyotomy for gastroparesis, complete division of septum without the risk of perforation in diverticular diseases of esophagus, restoration of esophageal lumen in long strictures, restoration of bowel movement in Hirschsprung’s disease, and then taking the concept to the next level of pure NOTES (natural orifice transluminal endoscopic surgery) by entering the peritoneal cavity and performing fundoplication. This review will discuss the history of TSE with brief discussion about the various applications and what has been achieved till present.
Keywords: third space; per oral endoscopic myotomyfundoplication; robotic; endoscopy